Valid publication of the name Eriobotrya × daduheensis (Malinae, Rosaceae) - Ding, Mingyan; Fan, Qiang; Guo, Wei; Shi, Shi; Liao, Wenbo (Phytotaxa, 2015)
“Eriobotrya prinoides Rehd. et Wils. var. daduheensis H. Z. Zhang” was not validly published by Zhang et al. because there was no Latin diagnosis or description and no specimen was indicated as type. Recent studies showed that it was a hybrid between Eriobotrya japonica and E. prinoides. “Eriobotrya × daduheensis (H. Z. Zhang) B.Tang” was proposed, but it was a nomen nudum. Eriobotrya × daduheensis H. Z. Zhang ex W. B. Liao, Q. Fan et M. Y. Ding is validated by giving a full description and designating the type specimens in this paper.